2019
DOI: 10.1590/0034-7167-2018-0289
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of the social network of young female transsexuals that live and deal with HIV/AIDS

Abstract: Objective: to analyze the social network of young female transsexuals who live with HIV/AIDS. Method: descriptive and exploratory study of qualitative approach, based on the Social Network Theory, developed in a Brazilian reference hospital for HIV/AIDS, with six transsexual women. Individual interviews were recorded and transcribed, and the data were subjected to analysis of similarities through the software program IRaMuTeQ. Results: the categories observed were: 1) dynamics of primary social network and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
5
Order By: Relevance
“…We observed the context of family conflicts due to the expression of female transgender gender identity in the youth period, which contributes to the fragility of support bonds and culminates in social exclusion. A study found a greater degree of vulnerability to marginalization due to the lack of emotional, structural, and financial support from their support network (27) .…”
Section: Discussionmentioning
confidence: 99%
“…We observed the context of family conflicts due to the expression of female transgender gender identity in the youth period, which contributes to the fragility of support bonds and culminates in social exclusion. A study found a greater degree of vulnerability to marginalization due to the lack of emotional, structural, and financial support from their support network (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Los profesionales de la salud, en particular los de Enfermería que integran la Atención Primaria de Salud (APS), pueden establecer un vínculo y un papel de referencia en el reconocimiento de la red de apoyo a los adolescentes transgénero y sus familias, a fin de considerar su contexto social y, a partir de ahí, , atender a las necesidades, en una perspectiva sociohistórica y cultural, y no solamente biológica, posibilitando la garantía de los derechos y la implementación de políticas de atención integral en la RAS (19) .…”
Section: Además De Las Directrices Nacionales Para Launclassified
“…Health professionals, especially those in Nursing who comprise Primary Health Care (PHC) can establish a link and benchmark in the recognition of the support network for transgender adolescents and their families, in order to consider their social context, and, according to that, meet their needs, in a socio-historical and cultural perspective, and not only biological, enabling the guarantee of the rights and consolidation of policies for the integral health care in HCN 19 .…”
Section: Introductionmentioning
confidence: 99%